Synthesis and analysis of ZnO and CdSe nanoparticles - Ashtaputre, S. S.; Deshpande, Aparna; Marathe, Sayali; Wankhede, M. E.; Chimanpure, J.; Pasricha, R.; Urban, J.; Haram, Santosh K.; Gosavi, S. W.; Kulkarni, S. K. (Pramana-Journal of Physics, 2005)
Zinc oxide and cadmium selenide particles in the nanometer size regime have been synthesized using chemical routes. The particles were capped using thioglycerol in case of ZnO and 2-mercaptoethanol in case of CdSe to achieve the stability and avoid the coalescence. Zinc oxide nanoparticles were doped with europium to study their optical properties. A variety of techniques like UV-Vis absorption spectroscopy, X-ray diffraction (XRD), photoluminescence (PL), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FT-IR) and transmission electron microscopy (TEM) were used to carry out structural and spectroscopic characterizations of the nanoparticles.
1st National Conference on Nanoscience and Technology, Pune, INDIA, MAR 07-08, 2005
Keywords: chemical capping; Doping; Nanoparticles; photoluminescence

Surface studies on benzophenone doped PDMS microstructures fabricated using KrF excimer laser direct write lithography - Kant, Madhushree Bute; Shinde, Shashikant D.; Bodas, Dhananjay S.; Patil, K. R.; Sathe, V. G.; Adhi, K. P.; Gosavi, S. W. (Applied Surface Science, 2014)
his paper discusses microfabrication process for benzophenone doped polydimethylsiloxane (PDMS) using laser lithography. KrF excimer laser of 248 nm with 20 ns pulse width at repetition rate of 1 Hz was used for microfabrication of undoped and benzophenone doped PDMS. The doped-PDMS shows sensitivity below 365 nm, permitting processing under ambient light. The analysis of etch depth revealed that doped PDMS shows self developable sensitivity at lower fluence of similar to 250 mJ/cm(2). The unexposed and exposed surface was studied using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and Scanning electron microscopy (SEM). Spectrocopic analysis indicated increase in C-O, C=O, Si-O-3 and Si-O-4 bonding at the expense of Si-C and Si-O-2 bonds of PDMS. In case of laser exposed doped-PDMS, removal of benzophenone from probe depth of spectroscopy was observed. Whereas the surface morphology of exposed and unexposed doped-PDMS was observed to be same, indicating clean development of PDMS micropattems. The present study indicates that addition of 3.0 wt.% benzophenone in PDMS enhance self development sensitivity of PDMS. The self developable results on doped-PDMS are quite encouraging for its potential use in point of care Lab-On-Chip applications, for fabricating micropattems using direct write laser lithography technology.
Keywords: Direct write laser lithography; Microfabrication; micropatterning; Poly(dimethylsiloxane) (PDMS)

Synthesis and luminescence of graphene-nano calcium sulphide composite - Sharma, Geeta; Patil, K. R.; Gosavi, S. W. (Materials Chemistry and Physics, 2014)
Graphene-nanocrystalline calcium sulphide has been synthesized using in-situ reduction of calcium salt and graphene oxide. Graphene oxide was prepared using Hummer's method. Surface morphology and crystal structure of samples were observed by transmission electron microscopy (TEM) and X-Ray diffraction (XRD). Ultra thin graphene and graphene oxide sheets with size ranging between tens to several hundreds of square nanometers are observed in TEM images. The TEM micrographs of G-CaS show that CaS particles are embedded in graphene sheets and the average particle size of CaS particles in the composite is less than 50 nm. The reduction in the intensity of various functional groups in FTIR spectrum also confirms the formation of graphene. The UV-Visible spectra of CaS shows absorption peak at 220 nm with a small shoulder at 250 nm whereas in G-CaS 220 nm absorption peak has reduced intensity and the shoulder at 250 nm has now shifted to 270 nm due to modification in the defect structure of CaS by graphene. CaS and G-CaS shows photoluminescence emission at 470 nm (lambda(exc.) = 375 nm) and 440 nm (lambda(exc.) = 350 nm) respectively, however emission intensity of G-CaS is relatively lower than CaS. Although the emission intensity is found to be lower than CaS, addition of CaS to graphene in G-CaS complex has made graphene luminescent. XPS spectra also indicate reduction of various oxygen containing functional groups in highly reduced graphene oxide and G-CaS. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Luminescence; Nanostructures; powder diffraction; Precipitation